2017
DOI: 10.1002/2016wr019064
|View full text |Cite
|
Sign up to set email alerts
|

Mixed populations and annual flood frequency estimates in the western United States: The role of atmospheric rivers

Abstract: The Bulletin 17B framework assumes that the annual peak flow data included in a flood frequency analysis are from a homogeneous population. However, flood frequency analysis over the western United States is complicated by annual peak flow records that frequently contain annual flows generated from distinctly different flood generating mechanisms. These flood series contain multiple zero flows and/or potentially influential low floods (PILFs) that substantially deviate from the overall pattern in the data. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 39 publications
(82 reference statements)
4
66
0
Order By: Relevance
“…It is not surprising to observe a difference in the number of AR days diagnosed by the two methods given differences in the physical variables, algorithms, and data sets/information (satellite versus reanalysis) used to diagnose ARs. Rutz et al () and Barth et al () also showed that IVT methods tend to diagnose more AR days than with IWV across the western U.S.…”
Section: Resultsmentioning
confidence: 96%
“…It is not surprising to observe a difference in the number of AR days diagnosed by the two methods given differences in the physical variables, algorithms, and data sets/information (satellite versus reanalysis) used to diagnose ARs. Rutz et al () and Barth et al () also showed that IVT methods tend to diagnose more AR days than with IWV across the western U.S.…”
Section: Resultsmentioning
confidence: 96%
“…This pattern reflects the spatial distribution of frequency of ARs and the increasing intensity of precipitation over high‐elevation terrain (Dettinger, ; McCabe et al, ; Neiman et al, ; Ralph & Dettinger, ; Rutz et al, ). While lowland streams on the Pacific Coast have lower rates of maximum runoff (e.g., Puget Trough, Willamette, and Sacramento River valley), annual maximum streamflow (peaks and mean daily) in these streams is still largely a response to ARs (Barth et al, ; Figure S1 in the supporting information).…”
Section: Discussion Of Conditional Flood Responses To Atmospheric Rivmentioning
confidence: 99%
“…Atmospheric rivers (ARs) are long (>2,000 km) corridors in the lower troposphere where water vapor is transported poleward at high rates that have been identified as the primary cause of flooding in the western United States (U.S.) (Barth et al, 2017;Dettinger & Ingram, 2013;Dettinger et al, 2011;Florsheim & Dettinger, 2015;Neiman et al, 2011Neiman et al, , 2013Ralph et al, 2006). Geographic variation in the frequency of ARrelated flooding across the western U.S. reflects the strong west-to-east gradient in AR-forced precipitation (Barth et al, 2017;Ralph & Dettinger, 2012;Rutz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are known as a major cause of extreme precipitation and flooding events in the western United States, especially along the west coast (Leung & Qian, ; Neiman et al, , ; Ralph et al, ; Ralph & Dettinger, ). Previous studies have established the relationship between ARs and the likelihood of hydrological extremes (Barth et al, ; Guan et al, ; Lamjiri et al, ; Ralph et al, ). For example, Ralph et al () found that all seven floods in the Russian River of coastal northern California between 1997 and 2006 were associated with landfalling ARs.…”
Section: Introductionmentioning
confidence: 99%